2015
DOI: 10.1016/j.otsr.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Pressure algometry is a useful tool to quantify pain in the medial part of the knee: An intra- and inter-reliability study in healthy subjects

Abstract: Level III. Prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 30 publications
5
42
0
3
Order By: Relevance
“…ICCs showed almost perfect reliability for the PPTs and substantial to almost perfect reliability for both ROM and MIMS. Similar ICCs have been reported for PPTs in both the upper-and lower extremities of both asymptomatic and patient populations [29], [37], [59][60][61].…”
Section: Plos Onesupporting
confidence: 82%
See 1 more Smart Citation
“…ICCs showed almost perfect reliability for the PPTs and substantial to almost perfect reliability for both ROM and MIMS. Similar ICCs have been reported for PPTs in both the upper-and lower extremities of both asymptomatic and patient populations [29], [37], [59][60][61].…”
Section: Plos Onesupporting
confidence: 82%
“…The above mentioned methods have been used to assess mechanical pain sensitivity and shoulder function in BCS [15], [26], [27], and have been reported as reliable in both asymptomatic [25], [28], [29] and patient populations [30][31][32]. However, little is known about the relative and absolute reliability of these methods in BCS with pain after treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous and intense nociceptive input from a damaged joint may contribute to sensitization by enhanced pain responses, the spread of pain to larger body areas, and outside the symptomatic joint [8,13,14]. Previous studies have demonstrated PPT to have a high relative reliability in various anatomical locations like knee [15,16], neck [17,18], and lower back [19,20] both in patients and in healthy humans. However, the reliability of PPT is influenced by factors such as gender, age, investigator and [19,21].…”
Section: Introductionmentioning
confidence: 99%
“…Assessing pressure pain threshold (PPT) is a way of quantifying sensitivity of deep structures to mechanical pain [ 20 , 21 ]. PPT has a good to excellent relative reliability in many anatomical locations such as neck [ 22 24 ], knee [ 25 ], temporalis and masseter muscles [ 26 , 27 ] and the low back region [ 28 – 31 ]. However, for this latter anatomical location, only few studies assessed PPT’s absolute reliability [ 31 – 35 ].…”
Section: Introductionmentioning
confidence: 99%